Antioxidant phenolic compounds recovery from Mangifera Indica L. by-products by supercritical antisolvent extraction - Scognamiglio, M. (2015)
Supercritical Antisolvent Extraction (SAE) was used in the recovery of antioxidant compounds from mango by-products. The antioxidant extract was obtained by solid-liquid extraction using aqueous acetone (80% v/v) and subsequent adsorption/desorption in C18 cartridge. Recovery of antioxidants was performed by SAE using SC-CO2 as antisolvent. The temperature and pressure parameters were varied in the range 35-45C and 8-15 MPa. The SAE process allowed the recovery of about 90% of the initial phenolic compounds, the best recovery was obtained at 40C and 10 MPa and the main compounds were mangiferin, isomangiferin, quercetin 3-O-galactoside, quercetin 3-O-glucoside, quercetin 3-O-xyloside, quercetin 3-O-arabinoside, quercetin and kaempferol. The product obtained was a dry powder, spherical nanoparticles with a particle diameter of 143 40 nm with an antioxidant activity of 851.9 ?Mol TE/g and a half inhibition concentration of DPPH radical of 90 ?g/mL. The analyses performed indicated that SAE processing of natural extracts is effective for improving the activity of natural antioxidant compounds by producing nanoparticles.